Lung Cancer: Biomarkers, Tyrosine Kinase Inhibitors and Monoclonal Antibodies - Made Putra Semadhi; Stefanus Layli Prasojo; Anandani Widarini (Cell and BioPharmaceutical Institute, 2017)
Lung cancer is the most contributor of cancer cause death in the world. Lung cancer is related to cigarette consumption and genetic factor. Nicotine derived nitrosamine ketone is the most important inducer of lung cancer associated with DNA Mutations resulting in the activation of Kirsten rat sarcoma viral (KRAS) oncogenes. DNA Mutation in Lung cancer is mostly presence by epidermal growth factor receptor (EGFR) mutations. There were seven potential biomarkers to detect early lung cancer, whereas carcinoembryonic antigen (CEA), neuron specific enolase (NSE), cytokeratin-19 fragments (CYFRA 21-1), alpha-fetoprotein (AFP), cancer antigen 125 (CA-125), CA-199 and ferritin. The use of biomarkers in combination can improve the accuracy in diagnosing lung cancer. Other biomarkers include KRAS mutations, B-type Raf kinase (BRAF) mutation, mesenchymal-epithelial transition factor (MET) amplification and Excision repair cross-complementing group 1 (ERCC1) can be used to see whether there are any genetic mutations that lead to lung cancer. Treatment of lung cancer with chemotherapy can be done using tyrosine kinase inhibitors and monoclonal antibodies.Keywords: lung cancer, DNA mutation, EGFR, KRAS, BRAF, MET, tyrosine kinase